Diagnóstico da dinâmica espacial no entorno das estações metroviárias de Belo Horizonte - Fernanda Ferreira Faria (2022)
Rail transport was very important in the history of the city of Belo Horizonte because it made it possible to arrive at materials during its construction through the Central Railroad of Brazil. During Brazilian industrial development, which occurred in the 1950s and 1960s, demographic expansion reached very high levels, reflecting unprecedented urban growth. The evident conflict between individual and collective transportation in the 1970s caused the need to restructure the city's traffic by the government, which favored the use of automobiles instead of public transport. The transport of subway sums of the capital did not have major investments, with only one operational line (Line 1), and a scenario of future expansion (Line 2 and later Line 3). The distribution of the 18 passenger stations in Belo Horizonte, along Line 1, generated subcenters, which led to changes in the dynamics of urban occupation, with attractors and repulsors, as well as transformations that impacted on socio-environmental, urban, and logistical population themes, which differ depending on the neighborhoods in which they are located. In this context, the objective of this research was to map a set of territorial behaviors, which occurred around the 18 subway stations of the capital, in a radius of 400 meters from a central point, analyzing qualitatively and quantitatively the influence on urban dynamics and landscape for a period of 20 years. The study was structured based on the hypothesis that subway stations are potential elements that induce urban transformation, which generate changes in the distribution of land use and occupation, replacing permeable areas with constructed spaces. Using geoprocessing tools, new maps of land use and occupation were elaborated, with the creation of classes that reflect the changes observed in the years 2002, 2011 and 2021, defined for analysis. In addition, the zoning of the Municipal Master Plan, both repealed legislation and of the current legislation, was analyzed since the Public Policy has a fundamental role to create mechanisms to promote the sustainable development of the city. The results showed that over the years, there was great loss of permeable surface and tree vegetation in place of the construction of large enterprises, also verifying the process of verticalization, and the single-family residences were replaced, by multifamily, motivated by the potentiation of the subcenters created around the subway stations. The study also analyzed the hypothesis that the behavior of landscape change dynamics could be similar for different subway stations. This proof can support the future planning of other stations and contribute to the gap that has existed so far in the literature.